Family takaful demand in Malaysia: Proposed theoretical framework and hypotheses developments - Norizan, Remli; Muhamad, Muda; Romzie, Rosman (2017)
This paper discusses the proposed theoretical framework and hypotheses development of a study on Family Takaful demand in Malaysia. It will elaborate on the theoretical framework, hypotheses and research design of the study. Relevant literatures reviewed for the theoretical framework i.e., the empirical studies of how one theorizes or logically plausible relationship between several factors or matters that have been identified as important for the study area. It rationalises the important of theoretical framework where it enables the researcher to hypothesize as well as to test the relationship between the variables involved in order to expand the understanding of the related research area of study. The dependent variable is Family Takaful demand, while the independent variables which will be studied are disposable income, saving rate, education level, efficiency, profitability and sizes of companies. This study is a hypothesis testing study which normally explains the nature of certain relationship among groups or the independence of two or more factors in a situation. The hypotheses development begins with the selection of macroeconomic factors followed by the managerial factors. Then, analysis for correlation and regression will be conducted statistically.